W.B. Yeats and the Muses - Hassett, Joseph M. (Oxford : Oxford University Press, 2010)
This text explores how Yeats perceived the women to and about whom he wrote some of his greatest poetry in terms akin to the Greek notion that a poet is inspired and possessed by the feminine voices of the Muses. Newly available letters and manuscripts are used to examine the creative process and interpret the poems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Yeats, W. B. -- 1865-1939 -- Criticism and interpretation; Yeats, W. B. -- 1865-1939 -- Relations with women; Women in literature